Reliability of a structure stricken by a tornado - Milan Holický (Acta Polytechnica CTU Proceedings, 2022)
A tornado may become a very dangerous climatic action for any structure, depending on the tornado intensity and extent of the structure. The origin of a tornado, its range and further activity appear to be unpredictable and completely random. The strike of a tornado to a structure depends on the tornado movement and the structure extent. The tornado intensity is specified by the wind speed, following observed damages and consequences. The probability of a tornado strike on a structure depends on the extent of the structure itself, on the tornado range, and the extent of the considered reference area, for which data concerning tornado appearance are available. The probability of failure of a structure is given by the product of the probability of contact of a tornado with the structure and the probability of exceeding the design speed of the tornado wind. The probability of exceeding the design wind speed depends on the assumed distribution of wind speed and the frequency of tornadoes during the required lifetime of the structure. The target failure probability of common structures presented in available documents is 10−6 per year, and 10−7 per year of structures in power plants. However, it is not clear how these criteria have been derived. Further development of reliability theory of tornado-stricken structures is recommended to be focused on the risk analysis of appropriate systems, of which the considered structures are elements, on the target failure probability, on detailed analysis of the probability distribution of tornado wind speed and their frequency during the required lifetime of the structures.